Handbook of Religion and the Asian City: Aspiration and Urbanization in the Twenty-First Century - Veer, Peter van der (University of California Press, 2015)
Handbook of Religion and the Asian City highlights the creative and innovative role of urban aspirations in Asian world cities. It does not assume that religion is of the past and that the urban is secular, but instead points out that urban politics and governance are often about religious boundaries and processions-in short, that public religion is politics. The essays in this book show how projects of secularism come up against projects and ambitions of a religious nature, a particular form of contestation that takes the city as its public arena.Questioning the limits of cities like Mumbai